兩性教育議題網路教材之設計與發展 : 以「兒童性侵害防治網」為例 The Development and Design of Web-based Instruction Courseware for Elementary Students on Gender Education - Shin-Yi Ling; Chiung-Sui Chang (Jiàoyù zīliào yǔ túshūguǎn xué, 2003)
資訊科技已為現今教育的趨勢，成為教育改革中的一個要點，如:日本在推動九年計劃，讓學生熟悉多媒體的學習環境；歐盟推動「資訊社會中的學習」計劃，加強網路的建構並訓練老師發展教學軟體；美國將所有中小學連上網際網路列為西元兩千年前應完成的優先工作；我國更於民國87年公佈 「國民教育階段九年一貫課程總綱綱要」，強調資訊科技融入各科教學。在「中小學資訊教育總藍圖總綱」，期望能夠透過資訊融入教學，達到「資訊隨手得，主動學習樂；合作創新意，知識伴終生」的願景。針對在傳統上我國中小學教師對於兩性教育議題感欠缺優質教材的需求下，筆者應用系統化教學設計原則，希冀設計符合學童的兩性議題的學習網站，破除過往的舊式觀念，營造出一個鼓勵邀請但不強迫的環境，讓教與學可以更為自然、順暢且提供教師一項教學資源的應用。 The purpose of this web-based instruction project was designed to fulfill the needs of elementary students regarding gender education issues. World-Wide-Web can be a very useful delivery tool to share information about activities and resources; support teacher s instruction; and train students to follow guidelines to have correct knowledge on gender-sex issues The process of instructional design of this web-based project was also described. Using Dick & Carey s ISD model this web-based courseware was developed and implemented in a very effective multimedia presentation way.